Projeto de eficiência energética e regularização de instalações elétricas clandestinas em condomínio residencial baixa renda - Piloto, Paula Thayse de Azevedo (Universidade do Vale do Rio dos Sinos, 2017)
This work aims to address the project of an energy concessionaire that seeks to regularize clandestine connections in a low income residential condominium along with energy efficiency actions. The regularization project will include the installation of 118 armored measuring boxes, which are required to carry out fraud in energy meters. The energy efficiency actions will include lectures for the community, substitution of 25,000 incandescent or fluorescent lamps for LED technology lamps and the installation of 1,000 heat recuperators (efficient shower). This project based on the company's guideline to reduce the number of clandestine connections and consequently the energy losses resulting from this type of act. Seeking to use the good project management practices proposed by PMBOK, the project is based on integration management plans, scope, time, costs, quality, resources, communications, risks and acquisitions.
Keywords: Energia; Perdas energéticas; Eficiência energética; Energy; Energy losses; Energetic efficiency